Is walking in daily life a moderate intensity activity in patients with chronic obstructive pulmonary disease? - Vitorasso, R.; Camillo, C. A. [UNESP]; Cavalheri, V.; Aparecida Hernandes, N.; Cortez Verceze, A.; Sant'Anna, T.; Ferreira Monteiro, F.; Ramos, E. M. C. [UNESP]; Pitta, F. (Edizioni Minerva Medica, 2012)
Background. So far there are no studies investigating whether the time spent walking in daily life by patients with COPD corresponds to an activity of at least moderate intensity according to the recommendations of the American College of Sports Medicine (ACSM). Aim. To quantify in patients with COPD the time spent/day in physical activity of at least moderate intensity according to the ACSM (TPA>moderate); and to compare their TPA>moderate with the total time spent walking/day in daily life (TW). Design. Cross-sectional study.Setting. Patients entering in a pulmonary rehabilitation program at a University Hospital in Brazil. Population. Seventy-three patients with COPD (FEV1) 40 +/- 15% pred; 65 +/- 9 years). Methods. TW and TPA>moderate were respectively assessed with the DynaPort and Sense Wear activity monitors for 12 hours/day during 2 days.Results. There was significant difference between TW and TPA>moderate (53 [36-80] versus 12 [3-33] minutes/day, respectively; P<0.0001). Although 84% of patients reached more than 30 minutes/day of TW, only 29% reached more than 30 minutes/day of TPA>moderate. TPA>moderate correlated modestly with TW (r= 0.52; P<0.0001).Conclusion. The majority of patients with moderatevery severe COPD walk more than 30 minutes/day; however this does not mean that they are physically active, since less than 1/4 of their time spent walking can be considered as moderate-intensity activity. Clinical rehabilitation impact. Moderate-intensity physical activity in patients with COPD is more reduced than previously known. There is a clear need to increase their daily physical activity and lead a higher proportion of this population to comply with the minimum recommendations.
Keywords: Pulmonary disease, chronic obstructive; Exercise; Motor activity; Sedentary lifestyle